Selective Inhibitor of the c-Met Receptor Tyrosine Kinase in Advanced Hepatocellular Carcinoma: No Beneficial Effect With the Use of Tivantinib? - Zhao, Shankun; Wu, Weizhou; Jiang, Hao; Ma, Lei; Pan, Chengyi; Jin, Chong; Mo, Jinggang; Wang, Liezhi; Wang, Kunpeng (Frontiers in Immunology, 2021)
Advanced hepatocellular carcinoma (HCC) remains a formidable health challenge worldwide, with a 5-year survival rate of 2.4% in patients with distant metastases. The hepatocyte growth factor/cellular-mesenchymal-epithelial transition (HGF/c-Met) signaling pathway represents an encouraging therapeutic target for progressive HCC. Tivantinib, a non-adenosine triphosphate-competitive c-Met inhibitor, showed an attractive therapeutic effect on advanced HCC patients with high MET-expression in phase 2 study but failed to meet its primary endpoint of prolonging the overall survival (OS) in two phase 3 HCC clinical trials. Seven clinical trials have been registered in the “ClinicalTrials.gov” for investigating the safety and efficacy of tivantinib in treating advanced or unresectable HCC. Eight relevant studies have been published with results. The sample size ranged from 20 to 340 patients. The methods of tivantinib administration and dosage were orally 120/240/360 mg twice daily. MET overexpression was recorded at 34.6% to 100%. Two large sample phase 3 studies (the METIV-HCC study of Australia and European population and the JET-HCC study of the Japanese population) revealed that tivantinib failed to show survival benefits in advanced HCC. Common adverse events with tivantinib treatment include neutropenia, ascites, rash, and anemia, etc. Several factors may contribute to the inconsistency between the phase 2 and phase 3 studies of tivantinib, including the sample size, drug dosing, study design, and the rate of MET-High. In the future, high selective MET inhibitors combined with a biomarker-driven patient selection may provide a potentially viable therapeutic strategy for patients with advanced HCC.